Strain improvement of penicillium janthinellum ncim 1171 for increased cellulase production - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Varma, Anjanikumar; Gokhale, D. V. (Bioresource Technology, 2007)
The strain of Penicilhuinjanthinellunt NOM 1171 was subjected to mutation involving treatment of Ethyl Methyl Sulfonate (EMS) for 24 h followed by UV-irradiation for 3 min. Successive mutants showed enhanced cellulase production (EMS-UV-8), clearance zone on Avicel containing plate (SM2) and rapid growth on Walseth cellulose agar plates containing 0.2% 2-deoxy-D-glucose (SM3). These mutants were transferred to Walseth cellulose plates containing higher concentration (1.5%) of 2-deoxy-D-glucose (SM4) in which only five mutants showed clearance zone on SM4. All these mutants showed approximately two-fold increase in activity of both FPase and CMCase in shake flask culture when grown on basal medium containing CP-123 (1%) and wheat bran (2.5%). The enzyme preparations from these mutants were used to hydrolyze Avicel. Higher hydrolysis yields of Avicel were obtained with enzyme preparations of EU1. This is the first report on the isolation and selection of mutants based on hydrolysis of Avicel, which is the most crystalline substrate. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 2-deoxy-D-glucose resistant mutants; cellulase activity; EMS and ultraviolet mutation; Penicillium janthinellum

Strain improvement of lactobacillus lactis for d-lactic acid production - Joshi, D. S.; Singhvi, M. S.; Khire, Jayant Malhar; Gokhale, D. V. (Biotechnology Letters, 2010)
Three mutants, isolated by repeated UV mutagenesis of Lactobacillus lactis NCIM 2368, produced increased d-lactic acid concentrations. These mutants were compared with the wild type using 100 g hydrolyzed cane sugar/l in the fermentation medium. One mutant, RM2-24, produced 81 g lactic acid/l which was over three times that of the wild type. The highest d-lactic acid (110 g/l) in batch fermentation was obtained with 150 g cane sugar/l with a 73% lactic acid yield. The mutant utilizes cellobiose efficiently, converting it into d-lactic acid suggesting the presence of cellobiase. Thus, this strain could be used to obtain d-lactic acid from cellulosic materials that are pre-hydrolyzed with cellulase.
Keywords: Cellobiose utilization; D-Lactic acid production; Lactobacillus lactis; Mutant; Sucrose (cane sugar)